Hardware and Software for Embedded Compact: Broadband Low Field NMR spectrometers (ECBLFNMR) - Louis-Joseph, Alain; Nauton, Alexis; Coupvent-Desgravier, Denis; Korb, Jean-Pierre (Diffusion Fundamentals, 2017)
Numerous compact NMR spectrometers have been designed for an easy measurement of proton NMR spectra. High sensitivity and resolution can be reached even with low field spectrometers (LFNMR) (i.e. 60 MHz), thanks to great improvements in electronic hardware, which open up a wide field of analytical quantification and relaxation applications. A specificity of Low field NMR spectrometer is the use of a permanent and cryogen free magnet technology, avoiding the need for weekly and expensive cryogenic services. Here we present and describe a low field NMR spectrometer fabricated in our laboratory. This spectrometer (ECBLFNMR) operates at basic resonant frequencies ranging from 1 to 60 MHz, with standard sample diameter (5-10 mm). All the embedded hardware is very compact and requires only a 24 V DC power supply, so this spectrometer is portable, easy to install and has a small footprint. This ECBFLNMR is dedicated to education and quantification, and enables low-field NMR research. It may be coupled with scientific experiments not requiring high magnetic fields.